Sharing as rescripting: Place manipulations on YouTube between narrative and social media affordances. (September 2015) - Georgakopoulou, Alexandra
Abstract: Drawing on sociolinguistic studies of language and place and on small stories insights and methods, I put forth rescripting as a social media-enabled practice of sharing that systematically exploits visual and/or verbal manipulations of the taleworld place of already circulated stories, so as to present the new tales as parody or satire of the originals. YouTube videos such as spoofs, memes, remixes, and mashups, form typical instances of rescripting, but other verbal activities should also be recognized as part of this practice, e.g. circulars of jokes about an incident on online blogs. Using as a case study a critical moment incident related to the Greek crisis that was repeatedly shared in social media, I examine rescripting as it occurs in the intersections between story making and social media affordances, arguing that it can productively open up the current sociolinguistic focus on resemiotizations of circulated activities. I show how changes in the place of the taleworld ultimately lead to changes in emplotment on the basis of the spatial semiotic repertoires associated with the new settings. Participation frameworks are decisively shaped by these changes, as commenters mainly engage with the current tale and telling, going along with the ostensibly 'fictional' scenarios and engaging in active storytelling, that is, creating further plots on their basis. I discuss the implications of rescripting place for the study of sharing practices and vernacular participation as well as for the study of place as constitutive of narrative plots. Highlights: Rescripting place as a social media-enabled practice of sharing. Rescripting place and resemiotization. Rescripting place as a key-choice in spoof videos, remixes and mash ups. Double consciousness in participation frameworks on YouTube. Multi-layeredness of taleworld and telling places in sharing.